The effect of religiousity, subjective normal and perception of halal labels on the interest of buying halal cosmetics with islamic branding as intervening variable - Wahyu Nasikhatul Khasanah; Fetria Eka Yudiana (Indonesian Journal of Islamic Economics Research, 2021)
The purpose of this study was to determine the effect of religiosity, subjective norms, and perceptions of halal labels on interest in buying halal cosmetics with Islamic branding as a variable. Samples were taken as many as 100 respondents with the Accidental Sampling technique. The analysis uses path analysis. The results of the test showed that religion had no positive and significant effect on buying interest. While subjective norms, perceptions of halal labels, and Islamic branding have a positive and significant effect on buying interest. Religiosity has no positive and significant effect on Islamic branding. While subjective norms and perceptions of halal labels have a positive and significant effect on buying interest. The results of the path analysis test show that religiosity and subjective norms have no effect on buying interest mediated by Islamic branding, while the perception of halal labels has an effect on buying interest mediated by Islamic branding.